"Conclusions about exposure to ETS and health that will be unhelpful to us": How the tobacco industry attempted to delay and discredit the 1997 Australian National Health and Medical Research Council report on passive smoking. (26th November 2003) - Trotter, L; Chapman, S
Abstract : Background: Major reviews of the health effects of passive smoking have been subjected to tobacco industry campaigns to refute the scientific evidence. Following the 1992 US Environmental Protection Agency review, the Australian National Health and Medical Research Council (NHMRC) initiated a review of the health effects of passive smoking. At the time of this review, evidence that environmental tobacco smoke causes disease was being increasingly accepted in courts of law and voluntary adoption of smoking restrictions was rapidly growing. Objective: To demonstrate how the tobacco industry attempted to delay and discredit the publication of a report on passive smoking that the tobacco industry anticipated to contain recommendations that would be unfavourable to their business. Methods: A search of tobacco industry documents on the Master Settlement Agreement websites was conducted using the terms and acronyms representative of the NHMRC review. Results: The tobacco industry sought to impede the progress of the NHMRC Working Party by launching an intensive campaign to delay and discredit the report. The main strategies used were attempts to criticise the science, extensive use of Freedom of Information provisions to monitor all activity of the group, legal challenges, ad hominem attacks on the credibility of the Working Party members, rallying support from industry allies, and influencing public opinion through the media. Conclusions: The Australian tobacco industry deliberately impeded the NHMRC Working Party's progress and successfully prevented the publication of the report's recommendations. The tobacco industry's motivation and capacity to disrupt the advancement of scientific knowledge and policy in tobacco control should be recognised and anticipated.